Goal-Directed Movement Enhances Body Representation Updating - Wen, Wen; Muramatsu, Katsutoshi; Hamasaki, Shunsuke; An, Qi; Yamakawa, Hiroshi; Tamura, Yusuke; Yamashita, Atsushi; Asama, Hajime (Frontiers in Human Neuroscience, 2016)
Body representation refers to perception, memory, and cognition related to the body and is updated continuously by sensory input. The present study examined the influence of goals on body representation updating with two experiments of the rubber hand paradigm. In the experiments, participants moved their hidden left hands forward and backward either in response to instruction to touch a virtual object or without any specific goal, while a virtual left hand was presented 250 mm above the real hand and moved in synchrony with the real hand. Participants then provided information concerning the perceived heights of their real left hands and rated their sense of agency and ownership of the virtual hand. Results of Experiment 1 showed that when participants moved their hands with the goal of touching a virtual object and received feedback indicating goal attainment, the perceived positions of their real hands shifted more toward that of the virtual hand relative to that in the condition without a goal, indicating that their body representations underwent greater modification. Furthermore, results of Experiment 2 showed that the effect of goal-directed movement occurred in the active condition, in which participants moved their own hands, but did not occur in the passive condition, in which participants’ hands were moved by the experimenter. Therefore, we concluded that the sense of agency probably contributed to the updating of body representation involving goal-directed movement.